Therapeutic efficacy of a three-component anthelmintic drug against cestodosis and nematodosis of small domestic animals - T. S. Filatova (Российский паразитологический журнал, 2024)
The purpose of the study therapeutic efficacy of combined anthelmintic drug on dogs and cats of different age groups naturally infected with cestodes and nematodes.Materials and methods. The study drug in the suspension form contains oxantel pamoate, pyrantel pamoate, praziquantel, and additives as active ingredients. The therapeutic efficacy of the drug was evaluated on 228 animals naturally infected with nematodes or cestodes in the Podolsk Experimental Production Base of the VNIIP – FSC VIEV. The animals were divided into experimental and control groups of 6 animals each. The experimental dogs and cats were administered the study drug while the control animals were not given the drug. Clinical examinations and laboratory tests of fecal samples were performed on days 10, 20 and 30 after the start of the experiment. The method of helminthoscopy was used to detect segments and helminthoovoscopy as per Fülleborn to detect helminth eggs/cocoons in animal fecal samples with their subsequent differentiation. The results were statistically processed by the Student method using Microsoft Excel 2016.Results and discussion. It was found that anthelmintic drug based on oxantel pamoate, pyrantel pamoate and praziquantel had high therapeutic efficacy against parasitism in dogs and cats of nematodes Toxocara spp., Toxascaris leonina, Trichuris vulpis, Uncinaria stenocephala, Ancylostoma spp. and cestodes Echinococcus spp. (except for cats), Mesocestoides spp., Taenia spp., Dipylidium caninum, and Diphyllobothrium latum. When the drug was used in the animals of different age groups, no side effects or complications were recorded.